2016
DOI: 10.1175/jas-d-15-0236.1
|View full text |Cite
|
Sign up to set email alerts
|

Ice Nucleating Particle Measurements at 241 K during Winter Months at 3580 m MSL in the Swiss Alps

Abstract: Ice nucleating particle (INP) concentrations were measured at the High Altitude Research Station Jungfraujoch, Switzerland, 3580 m above mean sea level during the winter months of 2012, 2013, and 2014 with the Portable Ice Nucleation Chamber (PINC). During the measurement periods, the research station was mostly located in the free troposphere, and particle concentrations were low. At temperature T = 241 K, INP concentrations in the deposition regime [relative humidity with respect to water (RHw) = 93%] were, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
109
3
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 102 publications
13
109
3
3
Order By: Relevance
“…The uncertainty in the AF for PINC and SPIN is 14 %. experiments with PINC revealed particle losses below 5 % (Boose et al, 2016); thus, these losses do not explain the observed difference between the CFDC (PINC) and immersion freezing (PIMCA-PINC, LACIS).…”
Section: Apparent Differences Between Immersion and Condensation Freementioning
confidence: 76%
See 1 more Smart Citation
“…The uncertainty in the AF for PINC and SPIN is 14 %. experiments with PINC revealed particle losses below 5 % (Boose et al, 2016); thus, these losses do not explain the observed difference between the CFDC (PINC) and immersion freezing (PIMCA-PINC, LACIS).…”
Section: Apparent Differences Between Immersion and Condensation Freementioning
confidence: 76%
“…In many field measurements CFDCs have been used for measurements of INP concentration at water-supersaturated conditions (e.g., DeMott et al, 2010DeMott et al, , 2016Tobo et al, 2013;Boose et al, 2016;Lacher et al, 2017) and are sometimes used to represent immersion freezing (e.g., DeMott et al, 2017). As water-supersaturated conditions in CFDCs should result in droplet formation followed by freezing at a constant temperature, CFDCs should simulate condensation freezing (see, e.g., Welti et al, 2014, for a discussion of possible condensation freezing mechanisms).…”
Section: Apparent Differences Between Immersion and Condensation Freementioning
confidence: 99%
“…Possible mechanisms to explain the observed variability of ICNC can only be discussed briefly, because meteorological parameters were not measured. Very localized high ice nucleation rates cannot explain the observed ICNC of several tens per liter at the observed temperature of −5 • C because the average concentration of ice nucleating particles observed at the nearby Jungfraujoch did not exceed 7 stdL −1 at −32 • C (Boose et al, 2016). Ice crystals may also fall into the cloud from an ice cloud lying above, which was observed on satellite pictures.…”
Section: Mixed-phase Casementioning
confidence: 93%
“…Several studies exist from airborne platforms (e.g., Bigg, 1967;Rogers et al, 1998;Prenni et al, 2009;DeMott et al, 2010;Avramov et al, 2011;Schrod et al, 2017) and ground-based observations (e.g., DeMott et al, 2003b;Chou et al, 2011;Ardon-Dryer and Levin, 2014;Mason et al, 2016;Boose et al, 2016a, b) quantifying the number concentration of INPs and identifying their potential sources. Typically, filter sampling with subsequent offline freezing methods, and online measurements with continuous-flow-diffusion chambers (CFDCs) are used as INP measurement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, this comes at the cost of a low temporal resolution since the sampling times of the filters often are on the order of a few hours or longer. CFDCs measure INP concentrations in real time with a higher temporal resolution, on the order of a few to tens of minutes (e.g., Rogers, 1988;Rogers et al, 2001;Chou et al, 2011), but their total sampling volume is lower, and their sensitivity to detect INPs is limited at low concentrations (Boose et al, 2016a). This in particular is challenging at low supercooling or in areas where INP concentrations are lower than 0.1-1 per standard liter (std L −1 ; normalized to standard T of 273 K and pressure, p, of 1013 hPa).…”
Section: Introductionmentioning
confidence: 99%